Stereoselective Synthesis of (Sulfonimidoyl)cyclopropanes with (R)-PhSO(NTs)CH2Cl and ,-Unsaturated Weinreb Amides: Tuning the of Selectivity between C-Cl and C-S Bond Cleavage - Shen, Xiao; Liu, Qinghe; Zhang, Wei; Hu, Jinbo (European journal of organic chemistry, 2016)
(Sulfonimidoyl)cyclopropanes have become the subject of special interest since they combine the advantages of two chemical leads (cyclopropane and sulfoximine). However, their synthesis is limited, and the stereoselective synthesis of optically enriched (sulfonimidoyl)cyclopropanes still remains an unsolved task. Here we report the first stereoselective (sulfonimidoyl)cyclopropanation reaction using ,-unsaturated Weinreb amides and (R)-PhSO(NTs)CH2Cl [(R)-1]. This reaction possesses a broad substrate scope, and the products can be easily transformed into other useful cyclopropyl-containing and/or sulfonimidoyl-containing compounds. The Weinreb amide group and the counter cation of the base were found to be important for the selective C-Cl bond cleavage.